Endoscopic filling with polyglycolic acid sheets and fibrin glue of persistent fistula after esophagectomy - Tashiro, Kousei; Takeno, Shinsuke; Kawano, Fumiaki; Kitamura, Eiji; Hamada, Rouko; Ikenoue, Makoto; Munakata, Shun; Nanashima, Atsushi; Nakamura, Kunihide (Endoscopy, 2020)
Background Treatment of anastomotic leakage in reconstruction after esophagectomy remains challenging. This report presents a new endoscopic filling method for persistent fistula after failure of conservative treatment of leakage caused by anastomotic insufficiency.Methods 10 of 14 patients, in whom post-esophagectomy leakage had failed to resolve after 2 weeks of conservative treatment, underwent endoscopic filling with polyglycolic acid (PGA) sheet and fibrin glue into the anastomotic leakage site, using a delivery tube and endoscopic catheter, respectively.Results Each patient underwent jejunostomy, to secure nutrition. The leakage was resolved in all 10 patients. The mean number of PGA – fibrin glue procedures was 1.7. The mean period from the first application to the resumption of oral intake was 31.6 days, from the final application it was 14.7 days.Conclusions The reported filling method offers a new endoscopic approach for persistent fistula after esophagectomy when conservative treatment of leakage has failed.